The uS8, uS4, eS31, and uL14 Ribosomal Protein Genes Are Dysregulated in Nasopharyngeal Carcinoma Cell Lines - Sim, E.U.H.; Ng, K.L.; Lee, C.W.; Narayanan, K. (Hindawi Publishing Corporation, 2017)
The association of ribosomal proteins with carcinogenesis of nasopharyngeal carcinoma (NPC) has been established in a limited subset of ribosomal protein genes. To date, three ribosomal protein genes, eL27 (L27), eL41 (L41), and eL43 (L37a), have been found to be differentially expressed in cell lines derived from NPC tumors. This raises the possibility of more ribosomal protein genes that could be associated with NPC. In this study, we investigated the expression profiles of eight ribosomal protein genes, uS8 (S8), uS4 (S9), eS31 (S27a), eL6 (L6), eL18 (L18), uL14 (L23), eL24 (L24), and eL30 (L30), in six NPC-derived cell lines (HONE-1, SUNE1, HK1, TW01, TW04, and C666-1). Their expression levels were compared with that of a nonmalignant nasopharyngeal epithelial cell line (NP69) using quantitative real-time PCR (RT-qPCR) assay. Of the eight genes studied, the expressions of four ribosomal protein genes uS8 (S8), uS4 (S9), eS31 (S27a), and uL14 (L23) were found to be significantly downregulated in NPC cell lines relative to NP69. Our findings provide novel empirical evidence of these four ribosomal protein genes as NPC-associated genetic factors and reinforce the relevance of ribosomal proteins in the carcinogenesis of nasopharyngeal cancer.